Implementasi Gaya Kepemimpinan Demokratis Dalam Organisasi - Aviana Noer Zubaida (STAI Publisistik Thawalib Jakarta, 2022)
The purpose of this research is to describe the implementation of leadership styles that can be carried out by leaders in organizations. This research method is qualitative with a Grounded Theory approach. Data collection techniques with documentation studies and data processing techniques with reduction, data presentation and drawing conclusions. The results showed: Implementation of the first idealized influence democratic leadership style, leaders are able to contribute good thoughts through decision making in achieving the vision of the organization. Second, inspirational motivation, leaders are able to encourage themselves and their subordinates to work according to the standards contained in the organization. Third, intellectual stimulation, the leader is able to move subordinates to continue to be creative by giving new and creative ideas that the leader has. The four individual considerations, leaders are able to appreciate and accept input and criticism from subordinates and appreciate the performance of subordinates.